EFEKTIVITAS PENERAPAN PENDEKATAN BERBASIS JENIS TEKS DALAM MENULIS TEKS ARGUMENTATIF - Indrayatti, Wahyu (Jurnal Kiprah, 2015)
This study is aimed to identifying four research problems related to the implementation of Genre Based Approach in the learning of writing argumentative texts. Those research problems are the implementation of Genre Based Approach in the learning of writing argumentative texts, the effectiveness of the implementation of Genre Based Approach in improving students’ writing skills, students’ writing skills after the implementation of Genre Based Approach, and students’ opinions and suggestions regarding the implementation of Genre Based Approach in the learning of writing argumentative texts. This study used a pre-experimental design with one group pre-test post-test.Data were collected by using writing tests and questionnaires. The subjects of this study were the fifth semester students of academic year 2012/2013 from Department of French Education, Indonesia University of Education. It was found that by using Genre Based Approach, the students read argumentative texts to enrich their knowledge, learn the examples of argumentative texts, wrote the argumentative texts in groups, and then wrote argumentative texts individually. The mean of post-testscores of the writing of argumentative texts increased about 26% (from 50,2 in pre-testto 63,35 in post-test). After the implementation of Genre Based Approach, students could write more vocabularies, could identify the events and experience clearly and more structured, and could make better arguments by explaining a fact or experience to support an argument. Based on data analysis, this study concluded that Genre Based Approach was effective to improve the students’ competence in writing argumentative texts. It is expected that this study will enrich studies regarding Genre Based Approach, and this approach can be implemented in the learning of writing all kinds of texts in class.